2023
DOI: 10.1097/md.0000000000032946
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology and bioinformatics study on the treatment of renal fibrosis with persicae semen-carthami flos drug pair

Abstract: To use network pharmacology and bioinformatics technology to reveal the mechanism of persicae semen-carthami flos drug pair in the treatment of renal fibrosis (RF). Compounds in traditional Chinese medicine were obtained through the Herb database. Appropriate compounds and corresponding drug targets were screened out based on the 5 rules of Lipinski and pharmacokinetics. Screening of suitable disease miRNAs by microarray chips in the GEO database. Find differentially expressed genes by analyzing miRNAs. Protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…This study found that the top two additive renoprotective collocations of A. sinensis in compounds were the use of Xue-Fu-Zhu-Yu-Tang and Shen-Tong-Zhu-Yu-Tang and the use of Shu-Jing-Huo-Xue-Tang and Shen-Tong-Zhu-Yu-Tang. These findings are consistent with previous studies ( Guo et al, 2013 ; Wang et al, 2023 ). The main bioactive compound of Xue-Fu-Zhu-Yu-Tang, Shu-Jing-Huo-Xue-Tang, and Shen-Tong-Zhu-Yu-Tang is Tao Ren [semen of Prunus persica (L.) Batsch], which is a potent anti-fibrotic agent that may have a therapeutic potential in patients with fibrotic kidney disease, as it can attenuate renal fibroblast activation and rat renal interstitial fibrosis ( Guo et al, 2013 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This study found that the top two additive renoprotective collocations of A. sinensis in compounds were the use of Xue-Fu-Zhu-Yu-Tang and Shen-Tong-Zhu-Yu-Tang and the use of Shu-Jing-Huo-Xue-Tang and Shen-Tong-Zhu-Yu-Tang. These findings are consistent with previous studies ( Guo et al, 2013 ; Wang et al, 2023 ). The main bioactive compound of Xue-Fu-Zhu-Yu-Tang, Shu-Jing-Huo-Xue-Tang, and Shen-Tong-Zhu-Yu-Tang is Tao Ren [semen of Prunus persica (L.) Batsch], which is a potent anti-fibrotic agent that may have a therapeutic potential in patients with fibrotic kidney disease, as it can attenuate renal fibroblast activation and rat renal interstitial fibrosis ( Guo et al, 2013 ).…”
Section: Discussionsupporting
confidence: 94%
“…The main bioactive compound of Xue-Fu-Zhu-Yu-Tang, Shu-Jing-Huo-Xue-Tang, and Shen-Tong-Zhu-Yu-Tang is Tao Ren [semen of Prunus persica (L.) Batsch], which is a potent anti-fibrotic agent that may have a therapeutic potential in patients with fibrotic kidney disease, as it can attenuate renal fibroblast activation and rat renal interstitial fibrosis ( Guo et al, 2013 ). Another common bioactive compound of Xue-Fu-Zhu-Yu-Tang and Shen-Tong-Zhu-Yu-Tang is Hong Hua ( Carthamus tinctorius L.), which also has therapeutic effects on renal fibrosis ( Wang et al, 2023 ). Given that oxidative stress, inflammation, and fibrosis are three well-documented mechanistic processes implicated in CKD pathogenesis ( Khan et al, 2022 ), A. sinensis alone can confer renoprotection as the main effect in clinical practice.…”
Section: Discussionmentioning
confidence: 99%